TTW Model Assisted by Rotating Wheel Media to Improve Elementary Students' Critical Thinking Ability - Rohmah, Nazila 'Ainur; Masfuah, Siti; Setiawan, Deka (Universitas Pendidikan Ganesha, 2020)
This study aims to improve students' critical thinking skills and student learning activities. After they applied the Think Talk Write learning models assisted by rotating wheel media on IV- grade students of SDN Talun 01 with 28 research subjects. This type of research was classroom action research. The research was conducted in two cycles, each cycle consisted of 4 stages, namely, planning, implementing, observing, and reflecting. The independent variable in this study was the Think Talk Write learning model assisted by the rotating wheel media, and the dependent variable was the skill to think critically. The instruments in this study were tests, interviews, observation, and documentation instruments. Data analysis techniques used in this study were quantitative analysis and qualitative analysis. The results of this class action research can be seen from the achievement of the following indicators, namely (1) critical thinking skills, classical completeness of pre-cycle students by 62% (less) and increased on the first cycle by 72% (less), and increased in cycle II by 85% (good). (2) Student learning activities in the first cycle, attitude field, were 73% (less) and increased in the second cycle by 86% (good). Then, student learning activities in the cycle I, skills field were 74% (less) and increased in cycle II by 87% (good). Furthermore, it can be concluded that the application of the Think Talk Write learning model assisted with the 7th theme rotating wheel media about the diverse beauty in my country on IV- grade students of SDN.